Cirurgia micrográfica de Mohs - De Ávila Reis, Nilton; Maluf Azevedo, Luciana Cirillo; Stolf, Hamilton Ometto [UNESP]; Nouri, Keyvan; Kimyai-Asadi, Arash; Goldberg, Leonard Harry (My University, 2011)
Mohs Micrographic Surgery is regarded as a very useful technique for the excision of difficult to han- dle skin cancers. The procedure is divided into clearly defined steps: tumor evaluation and marking, tumor exeresis, tissue preparation and mapping, histologic processing and analysis, and closing of the surgical wound. The histologic analysis of all surgical margins leads to higher cure rates and tissue conservation, which make the procedure safer and more reliable.
Mohs micrographic surgery
Keywords: Frozen sections; Mohs surgery; Skin neoplasms